Disagreeing About the Problem in PBL - Giajenthiran Velmurugan; Diana Stentoft; Jacob Gorm Davidsen (Journal of Problem Based Learning in Higher Education, 2021)
An essential part of Problem-Based Learning (PBL) is the students’ groupwork. What happens in students’ group work when no tutor/facilitator is present is normally a hidden land. Thus, there is limited research on students’ interactional way of doing PBL, this study tries to amend this by looking at how students conduct group work without any tutor/facilitator present. In this study, our research question is: How do students negotiate disagreements in their decision-making regarding their problem construction, and which element(s) in the interaction establishes if the decision is made or not? With a focus on students’ interactional work, we used video-observation to gather data of a 3rd semester Engineering Group at Aalborg University, Denmark. Our findings indicate that the conversation's structure has a profound impact on whether a decision proposal is accepted. Thus, the individual’s ability to hold on to their position and answer questions towards one’s proposal determines if other group members follow your suggestion. The study provides knowledge to an under-researched area of PBL and recommends a focus on PBL students’ interactional work in relation to near future cases of PBL.